2020
DOI: 10.1002/hpja.387
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy, digital health literacy and the implementation of digital health technologies in cancer care: the need for a strategic approach

Abstract: Issue addressed Digital health technologies can potentially reduce health disparities in cancer care. However, the benefits of digital health technology depend partly on users’ digital health literacy, that is, “capabilities and resources required for individuals to use and benefit from digital health resources,” which combines health and digital literacy. We examined issues for digital health technology implementation in cancer care regarding digital health literacy, via stakeholder consultation. Methods Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 27 publications
(46 reference statements)
2
78
0
1
Order By: Relevance
“…Other issues that need to be addressed include inadequate training of health care providers of skills in dealing with remote consultations to provide safe and effective patient care [9]. And, of course, the widespread use of resources, such as those demonstrated herein, is always dependent on patients' adequate technological literacy and internet access [27].…”
Section: Discussionmentioning
confidence: 98%
“…Other issues that need to be addressed include inadequate training of health care providers of skills in dealing with remote consultations to provide safe and effective patient care [9]. And, of course, the widespread use of resources, such as those demonstrated herein, is always dependent on patients' adequate technological literacy and internet access [27].…”
Section: Discussionmentioning
confidence: 98%
“…Previous interventions to improve DHL using a design similar to this study have shown that digital health technology facilitates access to health care and HL, providing opportunities to increase the scope and participation of patients in these types of interventions [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Technologies aimed at improving health outcomes for older adult populations as they transition across care settings have demonstrated success and promise [ 20 , 24 - 28 ]. Technologies to support care transitions can increase access to support for older adults as they transition from hospital-to-home by reducing architectural and physical barriers to accessing care in the community [ 20 , 29 , 30 ]. Other benefits of technology in supporting care during transitions include eliminating barriers to attending in-person support programs, such as restricted mobility, time constraints, transportation costs, and a lack of respite care for individuals caring for others [ 31 ].…”
Section: Introductionmentioning
confidence: 99%